Parole, mare e isole del Mediterraneo: Joan Estelrich nel ricordo di Josep Pla. - LO GIUDICE, IVAN (Scripta)
Joan Estelrich and Josep Pla's friendship allows us today to know a few more details about the life and personality of the intellectual from Felanitx, thanks above all to a common feature shared by the two friends: their passion for writing. In the case of Pla, mainly due to his work as a journalist and his inclination towards travel literature, while Estelrich may be described mainly as an essayist and diarist. The influence of the Mediterranean landscape and his weakness for traditional Majorcan food are just some of the elements which Pla highlighted in the remembrance of his friend when he included him among the 1959 Homenots. After all, Estelrich himself repeatedly stated the importance of the mare nostrum as an element of union among the peoples who inhabit its coasts and some of the main cultural projects he directed between the 20s and 30s actually included the idea of a common Mediterranean heritage to recover and safeguard. Further occurrences such as the launch of the newspaper El Día, the organization of the Setmana de la Saviesa in Formentor and the colourful description of one of Estelrich's countless ship crossings from Barcelona to Palma, highlight the importance of the sea and its islands in Estelrich's life: a man who used to observe everything from a cultural point of view and who always remained faithful to his roots in a life submerged in writings, travels and public relations.